2020
DOI: 10.1002/pd.5841
|View full text |Cite
|
Sign up to set email alerts
|

Discussing non‐invasive prenatal testing on Reddit: The benefits, the concerns, and the comradery

Abstract: Objective As the use of non‐invasive prenatal testing (NIPT) increases, its benefits and concerns are being examined through surveys, qualitative studies, and bioethical analysis. However, only scant research has examined public discourse on the topic. This research examined NIPT discussions on the social media platform Reddit. Method Content and qualitative description analysis was performed on 98 NIPT discussions (2682 comments), obtained by inputting “NIPT” into Reddit's search engine. Results Detailing of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…The Z-score distribution of true and false positives of these chromosomes may be helpful for clinical counseling. Pregnant women whose NIPS results indicate risk of fetal abnormality should be treated differently depending on their choice of follow-up confirmation testing: (1) pregnant women are usually anxious when they are informed of the risk indicated by the results ( Marcon et al, 2021 ). Pregnant women with a Z-score ≥ 3 and < the optimal cutoff value for T21 and T18 could be told about the possibility of false positive to alleviate anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…The Z-score distribution of true and false positives of these chromosomes may be helpful for clinical counseling. Pregnant women whose NIPS results indicate risk of fetal abnormality should be treated differently depending on their choice of follow-up confirmation testing: (1) pregnant women are usually anxious when they are informed of the risk indicated by the results ( Marcon et al, 2021 ). Pregnant women with a Z-score ≥ 3 and < the optimal cutoff value for T21 and T18 could be told about the possibility of false positive to alleviate anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…As the number of conditions that NIPT can test for increases, possibly to include nonmedical uses, creative counseling mechanisms will be required to help people critically reflect on their decision whether to have NIPT (and if so, to detect what) and to mitigate harms from information overload. Since a growing number of individuals rely on the internet and social media to search for information about NIPT, it may be effective for HCPs to use online platforms to engage with the target population (91).…”
Section: Counselingmentioning
confidence: 99%
“…While there were clearly issues with accessing information about the SCA online, participants in this study and another recent study reported finding connecting with parents of/people with SCAs through social media and/or support groups helpful (Riggan et al, 2021). Additionally, there is evidence that people having NIPT may seek and value information and opinions from social media or online forums (Marcon et al, 2021). These findings highlight the desire for real world, relatable perspectives of the condition.…”
Section: Discussionmentioning
confidence: 99%